Performance comparison of one cylinder combustion engine with variations of compression pressure & octane number gasoline - Rahmat, Bahtiar; Wijaya, Mohammad Burhan Rubai (Universitas Muhammadiyah Jakarta, 2023)
Nowadays, automobiles and motorcycles manufacturer produced more powerful and efficient engines. This engine usually has high compression pressure to achieve high performance and economic gasoline consumption. Unfortunately, only few people known that high compression engine requires high octane number gasoline. The aim of this research were to find out the differences of power & torsion output of one cylinder combustion engine which given several compression pressure variances using Pertamax & Pertamax racing gasoline. Dynamometer test has been carried out to find the performance difference of one cylinder combustion engine. The results shown that the highest compression pressure engine (11,8 Kg/cm2) using Pertamax racing gasoline (RON 100) produced highest power output at 7,8 KW with torsion output at 10 Nm. Meanwhile, the lowest compression pressure engine (10 Kg/cm2) using Pertamax gasoline (RON 92) produced lowest power output at 4,2 KW with torsion output at 3,8 Nm.